2022
DOI: 10.1186/s13690-021-00764-4
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: information access, trust and adherence to health advice among migrants in Norway

Abstract: Background Migrants in Norway bear a higher burden of COVID-19 infections and hospitalization as compared to non-migrants. The aim of our study was to understand how migrants perceive their own health risk, how they access information regarding the preventive measures, the degree of trust in this information, in the Norwegian authorities and the news media, and migrants’ adherence to authorities’ recommendations regarding the pandemic. Methods An o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 17 publications
0
21
0
1
Order By: Relevance
“…The proportion of immigrants considering themselves to be in a vulnerable group for COVID-19 has been shown to vary with country background. 24 Households with several generations living together are more common among immigrants than among Norwegian-born and could be one reason that elderly and vulnerable groups have not been able to keep social distance to a large degree. However, studies of secondary attach rate within households indicate that this is a phenomena but still has limited explanatory value.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proportion of immigrants considering themselves to be in a vulnerable group for COVID-19 has been shown to vary with country background. 24 Households with several generations living together are more common among immigrants than among Norwegian-born and could be one reason that elderly and vulnerable groups have not been able to keep social distance to a large degree. However, studies of secondary attach rate within households indicate that this is a phenomena but still has limited explanatory value.…”
Section: Discussionmentioning
confidence: 99%
“…The lower risk of COVID-19 in this group compared with other immigrants supports the hypothesis that language may play a role. Previous surveys in Norway suggest that immigrants generally perceive that they have access to the information they need, 24 , 26 but also that some information can be hard to understand. 22 Especially elderly immigrants without children nearby to help and newly arrived immigrants may have difficulties in accessing information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we do not have data on COVID-19 precautionary measures among foreign-born dentists, it is challenging to estimate the extent to which better or worse adherence to COVID-19 prevention and control measures influenced our findings. While previous studies 33 , 34 reported high adherence to COVID-19 recommendations among the foreign-born population in general, it remains unclear how different foreign-born HCWs responded to workplace COVID-19 prevention guidelines. Considering that dentists in this study had a lower HR for COVID-19 infection and a higher HR for COVID-19-related hospitalization than most other HCWs (also seen when the data were restricted to only the first wave), it is possible that they may be reasonably well-protected against infection, but if they get infected, the dose may be higher which could increase severity and hospitalization.…”
Section: Discussionmentioning
confidence: 90%
“…[ 35 ]. A Norwegian study found that most migrants reported a high level of adherence to preventive measures (88%) and trust in Norwegian authorities (79%) [ 36 ]. The study reports, however, that there were variations among groups regarding the importance of sources of information and level of trust, which was lowest for the Polish group.…”
Section: Discussionmentioning
confidence: 99%